Radioimmunological comparison of the DNA polymerases of avian retroviruses. - Bauer, G (J Virol, 1980)
125I-labeled DNA polymerases of avian myeloblastosis virus and spleen necrosis virus were used in a radioimmunological characterization of avian retrovirus DNA polymerases. It was shown that avian leukosis virus and reticuloendotheliosis virus DNA polymerases do not cross-react in radioimmunoassays. Within the avian leukosis virus species, species-specific and type-specific antigenic determinants of the DNA polymerase were defined. The previous finding of genus-specific antigenic determinants in avian myeloblastosis virus and Amherst pheasant virus DNA polymerases was confirmed and extended to members of all subgroups of avian leukosis virus. It was shown that there is little immunological variation between the DNA polymerases of the four members of the reticuloendotheliosis virus species. Particles with RNA-dependent DNA polymerase activity from the allantoic fluid of normal chicken eggs and from the medium of a goose cell culture did not compete for the antibodies directed against any of the sets of antigenic determinants defined in this study.